PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Egi Dwi Sriyani; Desy Purwasih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to analyze the effect of financial performance and dividend policy on firm value with capital structure as the intervening variable. This type of research is a quantitative research using secondary data population obtained from the Indonesia Stock Exchange and related websites for the 2016-2020 period, totaling 14 companies. The sampling technique in this study was using purposive sampling method with data analysis techniques used were panel data regression analysis and path analysis by selecting a regression model, classical assumption test, and hypothesis analysis using the Eviews 9 data processing program. Based on the test results, the research it states that the t test (partial), financial performance and capital structure affect firm value, while dividend policy has no effect on firm value. Through the Sobel test, it was found that capital structure was able to mediate the effect of the relationship between financial performance on firm value, but capital structure could not mediate the effect of dividend policy on firm value